2021
DOI: 10.3389/fpsyg.2021.741810
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teacher-Student Interpersonal Relations in Flipped Learning on Student Engagement

Abstract: Education, in essence, is an interactive activity in which teacher and student interactions construct a learning path to raise knowledge. However, it is evident that this learning path is not merely cognitive. Thus, the role of interpersonal relationships should not be taken for granted. Teacher-student relationships are among the salient factors in effective teaching. Factors such as these trigger achievement, motivation, and engagement in students (Martin and Dowson, 2009), with student engagement in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Earlier investigations have indicated that learner engagement is a fundamental component of enhancing the quality of education. Numerous investigations have proved the significant correlation between learner engagement and flipped learning approach (e.g., Afzali and Izadpanah, 2021 ; Li, 2021 ; Lee et al, 2022 ; Teo et al, 2022 ). In flipped learning, two modes of learning, pre-class and in-class, are based on a distinctly different approaches to knowledge and learning.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Earlier investigations have indicated that learner engagement is a fundamental component of enhancing the quality of education. Numerous investigations have proved the significant correlation between learner engagement and flipped learning approach (e.g., Afzali and Izadpanah, 2021 ; Li, 2021 ; Lee et al, 2022 ; Teo et al, 2022 ). In flipped learning, two modes of learning, pre-class and in-class, are based on a distinctly different approaches to knowledge and learning.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Establishing supportive interpersonal relationships promotes open communication, where students feel comfortable expressing difficulties and asking for assistance. Positive feedback in this process can then stimulate their motivation, fostering a sense of emotional well‐being and achievement in learning mathematics (Barile et al., 2012; Li, 2021). Students, with guidance and encouragement from their parents or teachers, are also more likely to persevere when faced with challenging tasks or setbacks (Koca, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the teacher-student relationship is a two-way interpersonal association that takes place in proximal (e.g., proactive interactions) and distal systems (e.g., the classroom environment; Zhou et al, 2020 ). When a supportive teacher-student relationship is established, students are more willing to express their ideas and collaborate with their peers, which stimulates students’ motivation, helps them experience a sense of well-being, and, in turn, achieves academic success ( Barile et al, 2012 ; Li, 2021 ). Further, when such students are faced with challenging tasks or setbacks, they are more likely to persevere, especially with the encouragement, feedback, and support of their teachers ( Koca, 2016 ).…”
Section: Introductionmentioning
confidence: 99%